Marketing study of a natural sweetener derived from stevia - Baltazar-Bernal, Obdulia; Zavala-Ruiz, Jesús; Spinoso-Castillo, José Luis (Revista Mexicana de Ciencias Agrícolas, 2025)
The stevia (Stevia rebaudiana Bertoni) plant is a natural non-nutritive non-caloric sweetener with various beneficial properties, among which its hypoglycemic, caloric and anxiolytic activities stand out. In Mexico, type 2 diabetes mellitus and obesity are some of the main public health problems. The objective of this study was to determine the feasibility of marketing an infusion made with dried and ground stevia leaves to people with type 2 diabetes mellitus and people with obesity in the locality of Córdoba, Veracruz, in 2022. To this end, a cross-tabulation was carried out with three variables (they would buy a stevia infusion, sex and age), and the market was segmented through a cluster analysis; likewise, the stevia infusion was made in the food science laboratory of the College of Postgraduates-Córdoba Campus and offered in 0.25 and 0.5 g filter bags for doses of 250 and 500 ml cups. As a result, 14% of both people with diabetes and people with obesity mentioned that they have knowledge about stevia and 6 and 3% of both groups have tried the plant. In conclusion, the general public had limited knowledge about the stevia plant; nevertheless, there is a potential demand for stevia infusion; therefore, the proposal to develop a stevia infusion for marketing to the target audience is viable.
Keywords: Stevia rebaudiana; non-caloric supplement; stevia dosage; stevia consumption